Seeking and engaging in psychotherapy: Investigating the comparative value of two models - Rumstein McKean, Orly (University of Ottawa (Canada), 2005)
This longitudinal study examined the predictive ability of the Theory of Self-Determination and the Transtheoretical Model of Change with respect to seeking and engaging in adult psychotherapy. Seeking therapy was operationalized by time (days between deciding to seek therapy and contacting a clinic), and difficulty (concerning this decision). Engagement was measured both behaviourally (attending at least three sessions of therapy) and psychologically (client rated alliance and satisfaction, and therapist rated alliance). To facilitate comparison between the models of motivation and change, the measures of these models were scored in identical ways (i.e., continuous full scale index scores, summary scale scores, and subscale scores). Modifications made to these measures and the implications of doing so are described. The study variables were examined with self-report data from 155 clients and 107 therapists at a community mental health clinic. Data were collected before the therapy began and after the third treatment session, providing both prospective and retrospective information. Hierarchical multiple regression (HMR) and sequential logistic regression (SLR) were used to test three sets of hypotheses and their corresponding research questions. Client rated alliance was significantly predicted by the full measure of motivation and by some of its scales (i.e., intrinsic subscale, identified regulation subscale, internal motivation summary scale). It was also predicted by the action subscale and the ready for change summary scale of the measure of change. Finally, client satisfaction was significantly predicted by the intrinsic motivation subscale. Further significant findings included the importance of the referral source and the waiting list. When clients were self-referred, they required less time but experienced more difficulty in seeking therapy. Also, the longer clients spent on the waiting list, the less likely they were to attend at least three sessions of therapy. The hypotheses of this study were generally not supported however several summary and subscales demonstrated predictive ability. Also, the serendipitous findings with respect to type of referral for therapy and length of time on the waiting list are noteworthy. The strengths and limitations of the study and the implications of these results for future research and clinical application are discussed.
Keywords: Psychology, Clinical.